Peran Injourney Tourism Development Corporation dalam Mengembangkan Destinasi Wisata Berkelanjutan di Kawasan Nusa Dua Bali - Sri Rizki Asti Karini, Rieke; Nalya Arum Fathanah; Utami, Widya; Fadhilan Burhannudin, Muhammad Zaki; Rachman, Syahwa Anisa; Farasya, Rakha; Putra, Mochamad Dio; Putra, Ravendra; Akbar, Muhamad Faiz; Waluya, Ariel Riksa (Manajemen dan Pariwisata, 2025)
The purpose of this research is to see how InJourney Tourism Development Corporation (ITDC) contributes to creating an environmentally friendly tourist destination in the Nusa Dua Bali. Sustainability tourism has been a major consideration in the development of Nusa Dua Bali, which is recognized as one of the major tourist attractions in Indonesia. This research uses descriptive qualitative research methods and uses secondary data sources. The results of this study show how ITDC collaboration and training initiatives empower local communities, support sustainable business practices, and build environmentally friendly infrastructure. In addition, ITDC actively promotes environmental conservation through a number of programs, including waste management and marine ecosystem preservation. The study concludes that ITDC has a responsibility to promote community engagement and knowledge of the value of sustainable tourism in addition to overseeing the physical development of the area. It is hoped that other developers will use these findings as a guide in creating tourist attractions that are not only financially successful but also environmentally friendly and sustainable.